Accounting knowledge management capabilities, accounting functional effectiveness and overall university performance : evidence from Malaysia - Freida, Ayodele Ozavize (2018)
University accounting function system reflects the strategic orientation of institutions and impacts institutional performance. As such, it is important to know the potential implications of the defined dimensions of knowledge management (KM) on the accounting function system to inform institutional KM decision-making activities. However, little is known in the literature on how and why KM infrastructure and process translate into outcome in institutional accounting practice to ensure proper KM design. Drawing upon the Resource-based theory (RBT) and past findings, the study developed an integrative accounting knowledge management (AKM) capability hierarchical model to address the gaps. Data were collected through a questionnaire survey of a purposive sampling of 272 accounting function staff in public research universities in Malaysia. The two-stage approach to hierarchical modelling was employed and the research model tested via partial least square structural equation modelling (PLS-SEM). Interestingly, the findings revealed that AKM infrastructure and process positively influences accounting functional effectiveness, and AKM process partially mediates the influence of AKM infrastructure. Also, the result showed that while accounting functional effectiveness partially mediate the effects of AKM infrastructure, it does fully for AKM process capabilities on overall university performance. This research is significant as it informs research and practice on the patterns of accounting related KM infrastructure and process capabilities that require extensive management attention in institutional KM design and how and why they impact effectiveness. The study contributes to theory development in KM and accounting literature using the Resource-based theory (RBT) and creates avenues for future research.